1997
DOI: 10.1002/(sici)1097-0215(19970807)72:4<664::aid-ijc19>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The paracrine role of tumour-derived mIL-4 on tumour-associated endothelium

Abstract: Interleukin-4 (IL-4) has been demonstrated to possess anti-tumourigenic properties in vivo which is initially attributed to the infiltration of eosinophils proposed to occur by IL-4 binding to its receptors on endothelial cells, thereby mediating eosinophil adhesion. We have investigated whether the binding of IL-4 to receptors on endothelial cells could elicit other biological responses which may also play a role in tumour inhibition, such as angiogenesis. We have demonstrated that mouse IL-4 (mIL-4) down-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…16,17 A specific anti-angiogenic action was demonstrated in C6 glioblastomas 18 and our results in 9L tumors confirm this observation. However, in the presence of dex, when immune responses are weakened while the anti-angiogenic action is maintained, the intracranial growth of the tumor increases, supporting the notion that the immune system is playing a major role in the therapeutic action of IL-4.…”
Section: Dexamethasone Inhibits Il-4 Action On Gliomas S Benedetti Et Alsupporting
confidence: 85%
“…16,17 A specific anti-angiogenic action was demonstrated in C6 glioblastomas 18 and our results in 9L tumors confirm this observation. However, in the presence of dex, when immune responses are weakened while the anti-angiogenic action is maintained, the intracranial growth of the tumor increases, supporting the notion that the immune system is playing a major role in the therapeutic action of IL-4.…”
Section: Dexamethasone Inhibits Il-4 Action On Gliomas S Benedetti Et Alsupporting
confidence: 85%
“…Rat C6 glioma cells are used as an established model for malignant glioma and rapidly form highly vascularised cerebral tumors. 8,9,21 Our results show that endogenous endostatin is biologically active, has an antiproliferative effect on endothelial cells in vitro and can reduce the tumor growth rate in vivo, which is associated with an inhibition of angiogenesis.…”
mentioning
confidence: 67%
“…PECAM and factor VIII-related 840 antigens detect vascular endothelial cells in tumours as previously described. 21,24 Vascular density was calculated by counting the number of vessels in 10 random standard fields (0.55 ϫ 0.4 mm) in 5 sections/tumor. 25 Intracranial tumor volumes were calculated from haematoxylin-and eosin-stained brain sections as previously described 10,25 as length ϫ width ϫ depth (mm 3 ) Ϯ standard error.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In vitro, IL-4 inhibited the migration of cultured bovine and human microvascular cells and suppressed the formation of tube-like structure by human umbilical vein endothelial cells (HUVEC) induced by vascular endothelial growth factor (VEGF) and bFGF (26). Moreover, Saleh et al observed that IL-4-induced inhibition of C6 rat glioma was accompanied by reduced levels of vascularization (27,28). Practically, multiple factors, including innate immune cells, T lymphocytes and angiostasis may contribute to tumor rejection mediated by exogenous IL-4.…”
Section: The Mechanism Of Exogenous Il-4-induced Tumor Rejectionmentioning
confidence: 99%